Reconfiguring Sanctions for Environmental Crimes Through the Application of Deferred Prosecution Agreements (DPAS) to Corporations Under Law Number 1 Of 2023 Concerning the Indonesian Criminal Code - Galih Saptriono Nugroho (Dalihan Na Tolu: Jurnal Hukum, Politik dan Komunikasi Indonesia, 2026)
The reform of Indonesia’s criminal law through Law Number 1 of 2023 on the Criminal Code reflects a significant shift in the orientation of punishment. Punishment is no longer viewed solely as a means of retribution, but also as an instrument of corrective, restorative, and rehabilitative justice. This shift is particularly important in the context of environmental crimes, as corporate environmental offenses generally cause extensive, systemic, and long-term harm to ecosystems as well as to surrounding communities. Although Law Number 32 of 2009 on Environmental Protection and Management has recognized corporate criminal liability and provides for additional penalties and corrective measures, its sanctioning framework still faces several problems, particularly the predominance of a retributive approach, the lack of integration of ecological restoration into the core of punishment, and the difficulty of establishing corporate fault. This article addresses two main issues. First, how is the sanctioning framework for corporate environmental crimes regulated under Law Number 32 of 2009 and Law Number 1 of 2023 on the Criminal Code? Second, what model of Deferred Prosecution Agreement (DPA) may appropriately be applied to reconfigure sanctions for corporate environmental crimes without undermining the principle of criminal liability? This study is normative legal research employing statutory, conceptual, and, to a limited extent, comparative approaches. The research relies on primary and secondary legal materials, which are analyzed qualitatively through a descriptive-analytical method. The findings show that the current sanctioning framework has not yet been fully capable of addressing the need for prompt, concrete, and measurable restoration of environmental harm. While the 2023 Criminal Code strengthens the legal basis for attributing criminal liability to corporations, it does not automatically resolve the problem of effective ecological recovery. In this context, a DPA may be considered as a model for reconfiguring sanctions, provided that it is designed in a strict and accountable manner, requiring formal acknowledgment of governance failure, measurable environmental restoration obligations, concrete recovery for affected communities, disgorgement of unlawfully obtained profits, and internal corporate compliance reform. With such a design, a DPA should not be understood as a form of penal leniency, but rather as a legal mechanism that places ecological restoration and corporate governance reform at the center of the criminal law response to environmental offenses.